Seasonal Nitrous Oxide Emissions From Hydroponic Tomato and Cucumber Cultivation in a Commercial Greenhouse Company - Karlowsky, Stefan; Gläser, Markus; Henschel, Klaus; Schwarz, Dietmar (Frontiers in Sustainable Food Systems, 2021)
Nitrous oxide (N2O) is considered as the most critical greenhouse gas (GHG) emitted by agricultural and horticultural food production. Hydroponic vegetable cultivation in greenhouse systems has a high potential for N2O emissions due to the intense application of nitrogen-containing fertilizers. Previous studies on model hydroponic systems indicate that N2O emissions per unit area can be several times higher than typically found during field cultivation. However, reliable data from production-scale hydroponic systems is missing. Here we report our findings from monitoring the N2O emissions in a commercial production greenhouse, located in the east of Germany, over a period of 1 year. We used the static chamber method to estimate N2O fluxes in the root zones of hydroponic tomato and cucumber cultures on rock wool growing bags with drip fertigation. Regular sampling intervals (weekly-biweekly) were used to calculate whole season cumulative N2O emissions and N2O emission factors (EFs) based on the amount of nitrogen fertilizer applied. Our results indicate that the seasonal N2O emissions from hydroponic greenhouse cultivation are considerably smaller than expected from previous studies. In total, we estimated average cumulative N2O emissions of 2.3 and 1.5 kg N2O–N ha−1 yr−1 for tomato and cucumber cultures, respectively. Average EFs were 0.31% for tomato cultivation with drain re-use (closed hydroponic system), and 0.13% for cucumber cultivation without drain re-use (open hydroponic system). These values lie below the general EF for N2O from agricultural soils, noted with 1% by the intergovernmental panel on climate change (IPCC). In conclusion, considering the high yield of greenhouse cultivation, hydroponic systems provide a way of producing vegetables climate-friendly, in terms of direct GHG emissions. Further attention should be given to reducing energy inputs, e.g., by using regenerative sources or thermal discharge from industrial processes, and to increasing circularity, e.g., by using recycling fertilizers derived from waste streams. Especially in urban and peri-urban areas, the use of hydroponics is promising to increase local and sustainable food production.